Mango anthracnose disease: the current situation and direction for future research - Dofuor, Aboagye Kwarteng; Quartey, Naa Kwarley-Aba; Osabutey, Angelina Fathia; Antwi-Agyakwa, Akua Konadu; Asante, Kwasi; Boateng, Belinda Obenewa; Ablormeti, Fred Kormla; Lutuf, Hanif; Osei-Owusu, Jonathan; Osei, Joseph Harold Nyarko; Ekloh, William; Loh, Seyram Kofi; et al. (Frontiers in Microbiology, 2023)
Mango anthracnose disease (MAD) is a dangerous disease of mangoes, with estimated yield losses of up to 100% in unmanaged plantations. Several species that constitute Colletotrichum complexes are implicated in MAD worldwide. All mangoes grown for commercial purposes are susceptible, and a resistant cultivar for all strains is not presently available on the market. The infection can widely spread before being detected since the disease is invincible until after a protracted latent period. The detection of multiple strains of the pathogen in the USA, Brazil, and China has prompted a significant increase in research on the disease. Synthetic pesticide application is the primary management technique used to manage the disease. However, newly observed declines in anthracnose susceptibility to many insecticides highlight the need for more environmentally friendly approaches. Recent progress in understanding the host range, molecular and phenotypic characterization, and susceptibility of the disease in several mango cultivars is discussed in this review. It provides updates on the mode of transmission, infection biology and contemporary management strategies. We suggest an integrated and ecologically sound approach to managing MAD.